RANCANGAN APLIKASI ANDROID UNTUK SISTEM PENJUALAN DI TOKO ROTI ASLI DENGAN METODE WATERFALL - Firmansyah, Yuan Satria; Utami, Wahyu Sri (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
Asli Bakery, located in Yogyakarta, faces challenges in recording transactions and inventory that are still done manually. This recording system consumes a lot of time and has a high risk of errors. To improve efficiency and accuracy, this research aims to develop an Android-based sales application that allows real-time management of product data, transactions, and recaps. The method used in designing the system is Waterfall, which includes the stages of needs analysis, design, development, and testing. The results showed that this application speeds up the recording process and minimizes errors, allowing direct access to information for employees and shop owners. The implementation of this system shows the ability of Asli Bakery to adapt to information technology, strengthen its market position, and improve services to customers.